2011
DOI: 10.1007/s00500-011-0784-2
|View full text |Cite
|
Sign up to set email alerts
|

Coevolution of lags and RBFNs for time series forecasting: L-Co-R algorithm

Abstract: This paper introduces Lags COevolving with Rbfns (L-Co-R), a coevolutionary method developed to face time-series forecasting problems. L-Co-R simultaneously evolves the model that provides the forecasted values and the set of time lags the model must use in the prediction process. Coevolution takes place by means of two populations that evolve at the same time, cooperating between them; the first population is composed of radial basis function neural networks; the second one contains the individuals representi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…As in (Parras-Gutierrez et al, 2012), the experimentation has been carried out using 20 data bases, most of then taken from the INE 1 . The data represent observations from different activities and have different nature, size, and characteristics.…”
Section: Experimental Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…As in (Parras-Gutierrez et al, 2012), the experimentation has been carried out using 20 data bases, most of then taken from the INE 1 . The data represent observations from different activities and have different nature, size, and characteristics.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…The L-Co-R method (Parras-Gutierrez et al, 2012), developed inside the field of ANNs, makes jointly use of Radial Basis Function Networks (RBFNs) and EAs to automatically forecast any given time series. Moreover, L-Co-R designs adequate neural networks and selects the time lags that will be used in the prediction, in a coevolutive (Castillo et al, 2003) approach that allows to separate the main problem in two dependent subproblems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on such an idea, a hybrid approach, integrating different technologies in a systematical way, can effectively take advantages of the respective merits of single models and offset the disadvantages [40]. Recent researches have repeatedly observed that hybrid models are significantly more efficient in prediction capability than single ones [12][13][14][15]17], and some current interesting works can refer to the hybrid L-Co-R algorithm (lags coevolving with radial basis function neural networks-RBFNs) [41,42] and hybrid decomposition-and-ensemble models (coupling decomposition and forecasting techniques) [13,15]. Therefore, this paper tries to formulate a novel hybrid searching algorithm for the parameter selection in the LSSVR by integrating the grid method and the GA, to guarantee the prediction accuracy for crude oil price forecasting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When adapting SVM to TSF, variable and model selection are critical issues [6] [23] [15]. Variable selection is useful to select the relevant time lags to be fed into the SVM.…”
mentioning
confidence: 99%